MORPHO-SEMANTIC ANALYSIS AND SEMANTIC SHIFT OF ENGLISH INTERNET SLANGS - Ismailova Kamola Rafikovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article examines morphological and semantic analysis of English internet slangs and the semantic shift of English internet slangs used in social media, and to identify the most common morphological process through word formation found in the lexical of English Internet slang, and to find the most common type of shift of meaning used by followers on social media. In addition, analyzing the semantic shift of English internet slangs by looking at the morphological and semantic features of the words.